the PENGARUH BRAND AMBASSADOR X DI INSTAGRAM TERHADAP MINAT BELI MELALUI CITRA MEREK PADA KOPI KENANGAN - Hanif Rafi Aufa; Akhmad Yunani (FEB Universitas Sam Ratulangi Manado, 2023)
Brand ambassador X was chosen by Kopi Kenangan as a figure that is expected to improve brand image and ultimately consumer buying interest in its products. Instagram is a social media platform that is widely known and is often used by brand owners as a promotional tool with endorsements by brand ambassadors. This study aims to examine the influence of brand ambassador X on purchase intention through the Kopi Kenangan brand image. By involving 100 samples, the influence between variables was tested by regression, while the mediating role of the brand image was tested by Sobel. The results of the regression test show that brand ambassador X has a significant effect on brand image, and conversely, brand image has no significant effect on purchase intention. The results of the Sobel test show that brand image does not mediate the influence of brand ambassador X on purchase intention.